PEMETAAN POLA SEBARAN SAMPAH BERDASARKAN JENIS DI WILAYAH PESISIR PANTAI KURI KABUPATEN MAROS SULAWESI SELATAN - Rahayu Abriani Sahar; Abdul Rauf; Hamsiah Hamsiah (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2020)
Mapping Pattern of Garbage Distribution by Type on the Kuri Coastal Coast of Maros Regency. This study aimed to identify and map the pattern of waste distribution based on the type and size of the Kuri coast and formulate a strategy for managing the distribution of waste patterns on the Kuri coast. The method used in this study is a questionnaire distribution method (questionnaire) carried out by way of giving questionnaires to the respondents, identification of waste, mapping using GPS and SWOT analysis to determine the direction of the strategy. The most dominant type of waste in each location was soft plastic waste with a percentage of 40.51% and based on a map of the distribution of marine garbage collection points in 2019 in the Kuri Caddi Hamlet, it is known that almost all over the coast bordering the sea contributes to the pollution of marine trash, especially rubbish Plastic. The direction of the management strategy was the first priority, namely : 1) Preparation and enforcement of waste management regulations in the form of PERDA or regulations covering sorting from prohibited sources and sanctions, 2) Oversight of oceanic waste reaching the shore and which will settle in waters and Assistance in the activities of garbage banks and composting.